Surgical Experience of the National Pediatric Medical Center in Treating Craniosynostosis (Herald of the National Children's Medical Center, 2025)
Craniosynostosis is a serious problem in pediatric neurosurgery that requires timely diagnosis and comprehensive treatment. Over the past four years, the National Children's Medical Center (NDC) of Tashkent has introduced modern surgical techniques and improved approaches to postoperative rehabilitation, which has allowed us to accumulate significant clinical experience in solving problems in this area. This work reflects the possibilities of combining advanced neurosurgical technologies and regionally specific measures aimed at improving early diagnosis and increasing patient adherence to treatment.
Keywords: craniosynostosis; pediatric neurosurgery; endoscopic surgery; helmet therapy; surgical outcomes